POWER, METALLURGICAL AND CHEMICAL MECHANICAL ENGINEERING THERMOELECTRIC EVENTS IN LIGHT-EMITTING BIPOLAR SEMICONDUCTOR STRUCTURES - P. A. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objective. The development of light-emitting bipolar semiconductor structures having a low level of parasitic heat release.Methods. A method for converting thermoelectric heat in bipolar semiconductor structures into optical radiation to divert the excess energy into the environment was developed. At the same time, the cooling effect on thermoelectric junctions remains. Instead of an inertial process of conductive or convective heat transfer, practically instantaneous heat removal from electronic components to the environment takes place.Results. As a result, light-emitting bipolar semiconductor structures will allow more powerful devices with greater speed and degree of integration to be created. It is possible to produce transparent LED matrices with a two-way arrangement of transparent solar cells and mirror metal electrodes along the perimeter. When current is applied, the LED matrix on one of the transitions will absorb thermal energy; on other electrodes, it will emit radiation that is completely recovered into electricity by means of transparent solar cells following repeated reflection between the mirror electrodes. The low efficiency of solar cells will be completely compensated for with the multiple passages of photons through these batteries.Conclusion. Light-emitting bipolar semiconductor structures will not only improve the reliability of electronic components in a wide range of performance characteristics, but also improve energy efficiency through the use of optical radiation recovery. Semiconductor thermoelectric devices using optical phenomena in conjunction with the Peltier effect allow a wide range of energy-efficient components of radio electronic equipment to be realised, both for discrete electronics and for microsystem techniques. Systems for obtaining ultra-low temperatures in order to achieve superconductivity are of particular value.